2020
DOI: 10.1007/s40259-020-00447-6
|View full text |Cite
|
Sign up to set email alerts
|

Switching to Biosimilar SDZ-ADL in Patients with Moderate-to-Severe Active Rheumatoid Arthritis: 48-Week Efficacy, Safety and Immunogenicity Results From the Phase III, Randomized, Double-Blind ADMYRA Study

Abstract: Background Sandoz adalimumab SDZ-ADL (GP-2017) is an approved adalimumab biosimilar with similar efficacy and comparable safety and immunogenicity to reference adalimumab (ref-ADL) as confirmed by analytical, pharmacokinetic and confirmatory studies. ADMYRA, a phase III double-blind study, was conducted with an aim to generate efficacy, safety and immunogenicity comparability data in patients with moderate-to-severe rheumatoid arthritis (RA) having inadequate response to disease-modifying anti-rheumatic drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 27 publications
2
67
0
1
Order By: Relevance
“…Previous studies demonstrated that GP2017 and Humira have identical amino acid sequences, indistinguishable secondary and tertiary structures, the same level of post-translational modifications, and a functional and pharmacological similarity to the reference drug (20,21). Wiland et al (22,23) conducted a phase III trial including 353 moderate-to-severe RA patients with inadequate response to disease modifying anti-rheumatic drugs. Patients were on a stable dose of MTX with biologics.…”
Section: Gp2017 (Hyrimoz/hefya/halimatoz)mentioning
confidence: 99%
“…Previous studies demonstrated that GP2017 and Humira have identical amino acid sequences, indistinguishable secondary and tertiary structures, the same level of post-translational modifications, and a functional and pharmacological similarity to the reference drug (20,21). Wiland et al (22,23) conducted a phase III trial including 353 moderate-to-severe RA patients with inadequate response to disease modifying anti-rheumatic drugs. Patients were on a stable dose of MTX with biologics.…”
Section: Gp2017 (Hyrimoz/hefya/halimatoz)mentioning
confidence: 99%
“…S1b). A total of 325 (92.1%) patients entered SP2 and 303 (85.8%) completed the study [ 24 ]. The SP1 and SP2 sets included 353 and 325 patients, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…HRQoL is reportedly impaired in IMIDs, including RA, PsA, and PsO [ 1 – 3 ]; PROs are therefore gaining considerable interest as they provide valuable evidence to inform clinical decision–making, pharmaceutical labeling claims, and health policies [ 10 13 ]. The primary results of the ADACCESS and ADMYRA studies demonstrated equivalent efficacy between SDZ-ADL and ref-ADL in patients with PsO [ 23 ] and RA [ 24 ], respectively. Results from the PROs assessed in the two studies confirm that both treatments lead to comparable improvements in HRQoL across the three diseases, PsO, PsA, and RA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations